A Novel Contact by a Novel Protein Complex Supports Cholesterol Transport to the Endoplasmic Reticulum. (June 2018) - Harada, Akihiro
Cholesterol is an essential component of membrane lipids and a starting material for hormone synthesis. After cholesterol is delivered to the cell as low-density lipoprotein, it is endocytosed and degraded in lysosomes to liberate free cholesterol. Free cholesterol is transported to the endoplasmic reticulum (ER) and esterified for further use. However, the mechanisms that transport cholesterol from lysosomes to the endoplasmic reticulum are poorly understood. We searched for binding proteins of a small GTP-binding protein, Rab11, and identified a novel protein, Rab11-binding protein containing LisH, coiled coil, and heat repeats (RELCH). RELCH also binds to oxysterol-binding protein (OSBP), an essential protein for nonvesicular cholesterol transport. The Rab11-RELCH-OSBP complex was found to tether to recycling endosomes and the trans-Golgi network, thereby mediating nonvesicular cholesterol transport between them. This pathway is distinct from the cholesterol transport pathway identified previously. In the absence of this complex, cholesterol accumulates in lysosomes in vitro and in vivo, suggesting the involvement of this complex in diseases associated with cholesterol transport.